Proteomics of loosely bound cell wall proteins of Arabidopsis thaliana cell suspension cultures: A critical analysis - Borderies, G.; Jamet, E.; Lafitte, C.; Rossignol, M.; Jauneau, A.; Boudart, G.; Monsarrat, B.; Monsarrat, B.; Boudet, A.; Pont-Lezica, R.
The complete sequencing of the Arabidopsis thaliana genome allows the use of the recently developed mass spectrometry techniques to identify the cell wall proteins (CWPs). Most proteomic approaches depend on the quality of sample preparation. Extraction of CWPs is particularly complex since the proteins may be free in the apoplast or are embedded in a polysaccharide matrix where they are retained by Van der Waals interactions, hydrogen bonds, hydrophobic or ionic interactions, or cross-linked by covalent bonds. Specific and sequential extraction procedures thus need to be developed. We report on the sequential extraction of loosely bound CWPs from living A. thaliana cells in culture. Different salts and chelating agents were used for releasing the proteins from the wall. Their effects on the extraction of CWPs and on the integrity of the plasma membrane were evaluated. Bioinformatic software was used to identify proteins and to predict their sub-cellular localization. The obtained data show that the plasma membrane of cells in culture was easily damaged by some steps of the extraction procedure, leading to the release of increasing amounts of intracellular proteins. Nevertheless, we identified fifty CWPs among which thirteen were new proteins for the cell wall. In addition, 76
Keywords: ARABIDOPSIS THALIANA; CELL SUSPENSION CULTURE; CELL WALL; MASS SPECTROMETRY; PROTEOMICS